THE IMPACT OF TEACHER-STUDENT RELATIONSHIPS ON STUDENT ACHIEVEMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teachers are perhaps the first and most significant fellowship that children generally expand outside the boundaries of their home. The role of the teachers indud residue powerful in an individual's life and that does not purely exist to schooling experience but goes fow beyond. A positive teacher-student relationship cause a positive impact on students learning outcomes, social conducts, and skillfulness growth. Studies have revealed that there lives a strong interrelationship between positive teacher-student relationship and student fulfilment. This is why cultivating a poitive rapport with students is always considered to be an essential aspect of characteristics teaching.